Performance of glass fiber‐reinforced cement composites containing phase change materials - Tuncel, Erman Yiğit; Pekmezci, Bekir Yılmaz (Wiley, 2018)
The use of solar energy has become a promising method to reach energy efficient solutions throughout the last century. Improving the thermal properties of building members will contribute to the efficient use of energy by preventing heat gain/loss through the building envelope. Phase change materials (PCMs) are favorable materials for thermal applications because of their large contribution to the thermal mass of a building and thus providing “inertia” against temperature fluctuations. In this experimental study, glass fiber‐reinforced cementitious composites were modified using a commercial microencapsulated PCM to improve their thermal performance. The thermal and the mechanical performances of the composites were investigated. With the use of PCMs, the latent heat capacity of the composites increased while the thermal conductivity decreased. Conversely, the mechanical properties of composites declined with increases in PCM amount. The main conclusions of the experimental study are as follows: PCMs provide a great potential to fiber‐reinforced cementitious composites to support the efficient use of energy, thereby enhancing the thermal features of the composites. The performance of PCM composites shows a serious variation according to different service temperatures. Therefore, the effect of service temperature must be considered particularly with respect to safe utilization of these materials. © 2018 American Institute of Chemical Engineers Environ Prog, 38:e13061, 2019